2010
DOI: 10.1111/j.1463-1326.2009.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profiles of a novel protein tyrosine phosphatase 1B inhibitor, JTT‐551

Abstract: JTT-551, a newly developed PTP1B inhibitor, improves glucose metabolism by enhancement of insulin signalling and could be useful in the treatment of type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
1
42
0
1
Order By: Relevance
“…The overexpression of PTP1B in muscle has been proposed to cause insulin resistance (21). Hepatic deletion and PTP1B inhibitors were shown to improve insulin resistance and reduce plasma glucose and TG levels in diabetic mice (14,22). The plasma concentrations of KY201 in OVX rats were compatible with PTP1B inhibitory concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of PTP1B in muscle has been proposed to cause insulin resistance (21). Hepatic deletion and PTP1B inhibitors were shown to improve insulin resistance and reduce plasma glucose and TG levels in diabetic mice (14,22). The plasma concentrations of KY201 in OVX rats were compatible with PTP1B inhibitory concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…PTP1B is known as a nonreceptor type tyrosine phosphatase and negatively regulates insu lin and leptin signaling (11,12). The genetic deletion or pharmacological intervention of PTP1B is known to have antidiabetic and antiobesity effects by amplifying insulin and leptin signaling, respectively (13,14). KY 201 was previously reported to reduce plasma glucose and triglyceride (TG) levels more effectively than rosi glitazone in KKA y mice, even though both compounds have similar human PPARg agonistic activities in COS1 cells (10), which suggests the involvement of PTP1B inhibition in its insulinsensitizing effects.…”
Section: Introductionmentioning
confidence: 99%
“…Ito et al reported the antiobesity effects of JTT-551, which was developed as a novel PTP1B inhibitor [85,19]. The single administration of JTT-551 and leptin enhanced STAT3 phosphorylation in the hypothalamus of DIO mice, and the food intake resulted in a significant reduction as compared with that in the control group.…”
Section: Protein Tyrosine Phosphatase 1b Inhibitormentioning
confidence: 99%
“…При пероральном введении JTT-551 у мышей линии ob/ob с генетически обусловленным ожирением и линии db/db с СД улучшался метабо-лизм глюкозы, предположительно благодаря усиле-нию инсулиновой сигнализации [57]. При хрониче-ском введении JTT-551 у мышей с ожирением, ин-дуцированным высококалорийной диетой, снижал-ся вес и нормализовался метаболизм липидов и глю-козы [58].…”
Section: активация и потенцирование инсулиновой сигна-лизации улучшеunclassified